EEG-based assessment of sustained attention in geriatric inpatients: a feasibility study - Lina Stagneth; Johanna Geritz; Gesine Hermann; Lea Dahl; Leoni Zuber; Christian Neumann; Josephine Lassen; Corina Maetzler; Cornelia Kranczioch; Julius Welzel; Walter Maetzler (GeroScience, 2026)
Sustained attention is a core cognitive function, frequently declines with age and neurological disease, and is highly relevant for functional outcomes in geriatric populations. Electroencephalography (EEG) offers high temporal resolution for assessing attentional processes, but its feasibility in multimorbid geriatric inpatients remains insufficiently characterized. This study evaluated the procedural and methodological feasibility of EEG-based sustained-attention assessments in geriatric inpatients undergoing early rehabilitative geriatric complex treatment (ERGCT). Geriatric participants completed standardized neuropsychological testing and two computerized attention tasks, the Psychomotor Vigilance Task (PVT) and a cued Go-NoGo task, during 32-channel EEG recording, including a resting-state recording. Feasibility was assessed using procedural indicators (recruitment, task completion, follow-up participation) and methodological indicators of EEG data quality, specifically the signal-to-noise ratios (SNR) and identification of expected event-related potential (ERP) components (P100, P300). Of 173 patients referred to the ERGCT programme, 43 could be included. Of those, 38 could undergo structured cognitive testing, and resting-state EEG and task-evoked ERPs could be recorded with adequate signal quality However, procedural feasibility was limited by substantial selection and attrition, resulting in incomplete protocol completion. Exploratory analyses suggest an association between higher resting-state alpha-band signal quality and faster PVT reaction times, whereas no associations were observed with global cognition, executive function, or age. Overall, resting-state and task EEG measures of sustained attention could be acquired with adequate data quality only in a selected subgroup of geriatric inpatients, who were able to participate in structured cognitive assessments, while extended and repeated assessment protocols were constrained by procedural burden, suggesting that EEG-based follow-up assessments are difficult to implement under current clinical conditions.

Unravelling cumulative effects of human pressures on demersal fish traits using a driver-pressure-state-impact framework - Jennifer Rehren; W. Nikolaus Probst; Casper Kraan; Hermann Neumann; Shubham Krishna; Matthias Hasenbein; Serra Örey; Kim Ludwig; Kai W. Wirtz; Carsten Lemmen; Antje Gimpel; Vanessa Stelzenmüller (Marine Environmental Research, 2026)

Conservation potential of offshore windfarms for epibenthic invertebrates and fish communities in a heavily used regional sea - W. Nikolaus Probst; Jennifer Rehren; Casper Kraan; Holger Haslob; Hermann Neumann; Carsten Lemmen; Shubham Krishna; Maren Kruse; Kai Wirtz; Vanessa Stelzenmüller (Biological Conservation, 2026)

Long-term common trends in epifauna communities and associated demersal fish assemblages mediated by environmental and human stressors in the south-eastern North Sea - Anja Singer; Ingrid Kröncke; Kim E. Ludwig; Hermann Neumann; Anne F. Sell (Estuarine, Coastal and Shelf Science, 2025)

Comparative analysis of bottom trawl and nanopore sequencing in fish biodiversity assessment: The sylt outer reef example - Yassine Kasmi; Hermann Neumann; Holger Haslob; Tina Blancke; Benita Möckel; Ute Postel; Reinhold Hanel (Marine Environmental Research, 2024)

Thresholds of seascape fauna composition along gradients of human pressures and natural conditions to inform marine spatial planning - Casper Kraan; Holger Haslob; Wolfgang N. Probst; Vanessa Stelzenmüller; Jennifer Rehren; Hermann Neumann (Science of The Total Environment, 2024)

Bayesian analysis of biodiversity patterns via beam trawl versus video transect—a comparative case study of Svalbard rhodolith beds - Eileen Straube; Hermann Neumann; Max Wisshak; Gregor Mathes; Sebastian Teichert (Biodiversity and Conservation, 2024)
Knowledge of spatial biodiversity patterns is important for ecosystem assessment. Rhodoliths, free-living calcareous algae, are biotic components that structure the sea floor through their complex calcareous skeletons and their tendency to accumulate in an area to form rhodolith beds. Thereby, rhodoliths are considered to act as ecosystem engineers promoting local biodiversity. In this study, the biodiversity of rhodolith beds in Mosselbukta, Svalbard, was investigated to analyse the proposed link between local biodiversity and the presence of rhodoliths by evaluating beam trawl and underwater video transect data. The comparative analysis of two sampling methods addressing the same research question allowed us to assess the suitability of these two methods. To test our hypothesis and the utility of the two methods, evaluations of the two data sets were carried out separately by using Bayesian statistics. The results confirm a positive relationship between the presence of rhodoliths and local biodiversity with a posterior probability of 70% for the video transects and 85% for the beam trawl data. The similarity of the results of the two methods suggests that both methods are well-suited for the analysis of local biodiversity patterns. The combination of the two methods, with their individual strengths and weaknesses, has provided stronger support for the results and a broader view on different components of the biodiversity in the Svalbard rhodolith beds.

Stepwise, earthquake-driven coastal subsidence in the Ganges–Brahmaputra Delta (Sundarbans) since the eighth century deduced from submerged in situ kiln and mangrove remnants - Till J. J. Hanebuth; Hermann R. Kudrass; Anja M. Zander; Humayun Syed Akhter; Gertrud Neumann-Denzau; Anwar Zahid (Natural Hazards, 2022)

Effects of Nutrient Management Scenarios on Marine Eutrophication Indicators: A Pan-European, Multi-Model Assessment in Support of the Marine Strategy Framework Directive - René Friedland; Diego Macias; Gianpiero Cossarini; Ute Daewel; Claude Estournel; Elisa Garcia-Gorriz; Bruna Grizzetti; Marilaure Grégoire; Bo Gustafson; Sofia Kalaroni; Onur Kerimoglu; Paolo Lazzari; et al. (Frontiers in Marine Science, 2021)
A novel pan-European marine model ensemble was established, covering nearly all seas under the regulation of the Marine Strategy Framework Directive (MSFD), with the aim of providing a consistent assessment of the potential impacts of riverine nutrient reduction scenarios on marine eutrophication indicators. For each sea region, up to five coupled biogeochemical models from institutes all over Europe were brought together for the first time. All model systems followed a harmonised scenario approach and ran two simulations, which varied only in the riverine nutrient inputs. The load reductions were evaluated with the catchment model GREEN and represented the impacts due to improved management of agriculture and wastewater treatment in all European river systems. The model ensemble, comprising 15 members, was used to assess changes to the core eutrophication indicators as defined within MSFD Descriptor 5. In nearly all marine regions, riverine load reductions led to reduced nutrient concentrations in the marine environment. However, regionally the nutrient input reductions led to an increase in the non-limiting nutrient in the water, especially in the case of phosphate concentrations in the Black Sea. Further core eutrophication indicators, such as chlorophyll-a, bottom oxygen and the Trophic Index TRIX, improved nearly everywhere, but the changes were less pronounced than for the inorganic nutrients. The model ensemble displayed strong consistency and robustness, as most if not all models indicated improvements in the same areas. There were substantial differences between the individual seas in the speed of response to the reduced nutrient loads. In the North Sea ensemble, a stable plateau was reached after only three years, while the simulation period of eight years was too short to obtain steady model results in the Baltic Sea. The ensemble exercise confirmed the importance of improved management of agriculture and wastewater treatments in the river catchments to reduce marine eutrophication. Several shortcomings were identified, the outcome of different approaches to compute the mean change was estimated and potential improvements are discussed to enhance policy support. Applying a model ensemble enabled us to obtain highly robust and consistent model results, substantially decreasing uncertainties in the scenario outcome.

Epibenthos Dynamics and Environmental Fluctuations in Two Contrasting Polar Carbonate Factories (Mosselbukta and Bjørnøy-Banken, Svalbard) - Max Wisshak; Hermann Neumann; Andres Rüggeberg; Janina V. Büscher; Peter Linke; Jacek Raddatz (Frontiers in Marine Science, 2019)

The effect of temperature variability on ecological functioning of epifauna in the German Bight - Hermann Neumann; Ingrid Kröncke (Marine Ecology, 2011)
Benthic epifauna was sampled in an area of 10 × 10 nautical miles in the German Bight. Samples were taken in January and July/August from 1998 to 2009. The ecological functioning of the epifaunal community was assessed using biological traits analysis (BTA). Twelve ecological traits of 26 epifaunal species were considered and analysed using non‐metric multidimensional scaling (nmMDS). Anomalies in the sea surface temperature (SST) close to the study area were mainly above the long‐term mean during the study period. SST was exceptionally high during the autumn months between 2002 and 2006. Additionally, the cold winter of 1995–96 was clearly reflected in strong negative SST anomalies. Trait composition changed in 2002, mainly due to a decreasing trend of traits related to an opportunistic life mode from 1998–2002. Traits related to reproduction showed a much clearer response to the high autumn SST anomalies from 2002 to 2006 than other traits. We concluded that the cold winter resulted in an increase in opportunistic species in the study area followed by characteristic post‐disturbance succession stages to the point of an established community in 2002. This indicates a recovery time of epifaunal communities in the German Bight of 7–8 years. Additionally, the results give evidence that climate‐induced variability of SST in the German Bight affects mainly the reproduction of epifaunal species rather than other traits such as feeding type.

Variability of epifauna and temperature in the northern North Sea - Hermann Neumann; Siegfried Ehrich; Ingrid Kröncke (Marine Biology, 2009)

Cells of Pseudomonas putida and Enterobacter sp. adapt to toxic organic compounds by increasing their size - Grit Neumann; Y. Veeranagouda; T. B. Karegoudar; zlem Sahin; Ines Musezahl; Nadja Kabelitz; Uwe Kappelmeyer; Hermann J. Heipieper (Extremophiles, 2005)

Changes in the classification of carcinogenic chemicals in the work area - Hans-Gnter Neumann; Spyridon Vamvakas; Heinz Walter Thielmann; Hans-Peter Gelbke; Johannes G. Filser; Ulrike Reuter; Heelmut Greim; Hermann Kappus; Klaus H. Norpoth; Peter Wardenbach; H.-Erich Wichmann (International Archives of Occupational and Environmental Health, 1998)